(untitled) (International Journal of Engineering and Computer Science, 2013)
Palm Print is one of the relatively new physiological biometrics, attracted the researchers due to its stable and unique characteristics. The rich feature information of palm print offers one of the powerful means in personal recognition. Palm print verification System has long been used and it was found that many research activities were carried out. This paper introduces the active shape model and touch less hand geometry.